"I Didn't Realize How Hard It Would Be!": Tensions and Transformations in Becoming a Teacher. (3rd May 2017) - Sydnor, Jackie
ABSTRACT: This study explores the experience of becoming an elementary teacher in an educational climate where standardization and accountability increasingly affect what happens in classrooms across the country by following two beginning teachers. Specifically, this longitudinal study in which two first-year teachers' stories are analyzed and restoried explores the tensions involved in becoming a teacher. This research, which focuses on the transition from student to teacher, illuminates the multiple discourses beginning teachers must negotiate as they determine the kind of teacher they will become. Based on the findings, recommendations are provided for how teacher education programs can better prepare beginning teachers, particularly those operating in reductive classrooms and forced to implement standardized curriculum. These implications for practice include (1) encouraging preservice teachers to be thoughtfully adaptive by creating and revising clear visions, (2) consciously creating zones of contact in which preservice teachers gain practical experience navigating competing discourses, and (3) critically examining field placements for preservice teachers.